Police legitimacy and procedural justice for children and youth: a scoping review of definitions, determinants, and consequences - Li, Jessica C. M.; Zhang, Serena Y.; Sun, Ivan Y.; Ho, Albert S. K. (Frontiers in Sociology, 2024)
IntroductionUnderstanding police legitimacy among children and youth is important for building a just and democratic society. Although the volume of studies on police legitimacy among underaged persons has grown in recent decades, the findings on the relationships between police legitimacy and procedural justice and their definitions, associated determinants, and consequences remain heterogeneous across studies and across political and legal contexts. Given these heterogeneities, the conclusions and implications generated by this research are far from comprehensive.MethodThis scoping review offers readers a comprehensive and comparative understanding of this topic by answering the following questions. (1) How can we define police legitimacy and procedural justice for children and youth? (2) What are the determinants of police procedural justice and legitimacy for children and youth? (3) What are the consequences of police procedural (in)justice and (il)legitimacy for children and youth? (4) Among children and youth, who are the vulnerable groups receiving less legitimate and unjust treatment from the police? A scoping review of the literature published between January 1, 1990 and May 31, 2022 was conducted based on four databases: PubMed, Web of Science, Scopus, and ProQuest. Guided by the scoping review screening framework proposed by Arksey and O’Malley, that is, the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines, and the checklist provided by the Joanna Briggs Institute for quality assessment, 47 publications, consisting of 38 quantitative studies and 9 qualitative studies, were retained in the final sample.ResultsThe results synthesize the operational and subjective interpretations of police legitimacy offered by the respondents in the studies reviewed which is followed by the discussion of conceptual and measurement issues. The key correlates of police legitimacy identified in these studies were police procedural justice and behavior, followed by experience and contact with the police, relationships with other authority figures, and personal competence in moral reasoning and self-control. In addition to compliance and cooperation, cynicism, trust, and health were related to police (il)legitimacy.DiscussionWe argue that in addition to building and maintaining police legitimacy, it is vital to remedy the negative consequences of injustice in police–youth encounters.Systematic Review Registrationhttps://inplasy.com/inplasy-2024-9-0064/, INPLASY202490064.